Comparison of ESSDAI and ClinESSDAI in potential optimisation of trial outcomes in primary Sjögren’s syndrome: examination of data from the UK Primary Sjögren’s Syndrome Registry (Swiss Medical Weekly, 2018)
OBJECTIVES To assess the use of the Clinical EULAR Sjögren’s Syndrome Disease Activity Index (ClinESSDAI), a version of the ESSDAI without the biological domain, for assessing potential eligibility and outcomes for clinical trials in patients with primary Sjögren’s syndrome (pSS), according to the new ACR-EULAR classification criteria, from the UK Primary Sjögren’s Syndrome Registry (UKPSSR). METHODS A total of 665 patients from the UKPSSR cohort were analysed at their time of inclusion in the registry. ESSDAI and ClinESSDAI were calculated for each patient. RESULTS For different disease activity index cut-off values, more potentially eligible participants were found when ClinESSDAI was used than with ESSDAI. The distribution of patients according to defined disease activity levels did not differ statistically (chi2 p = 0.57) between ESSDAI and ClinESSDAI for moderate disease activity (score ≥5 and